Kinematic characterization of backhand stroke accuracy in squash based on kinematic variables between two different skill levels—a preliminary cross-sectional study - Huang,Rui; Li,Haojie; Jiang,Jian; Zhou,Zhitao; Xiu,Chen (PeerJ, 2024)
Background The aim of this study was to compare differences in shot placement and accuracy between national and international level squash players. Squash is a technically demanding sport and understanding the biomechanical characteristics of athletes at different levels is important for developing effective training strategies. Methods The study used a three-dimensional motion analysis system, a high-speed video camera, and a professional tee for biomechanical testing. Participants included national and international level squash players. The kinematic characteristics of the shoulder, elbow, and wrist joints of the upper extremity for backhand strokes, as well as the accuracy of the strokes, were analyzed to compare the differences between the two groups of athletes in terms of stroke posture and accuracy. Results The kinematic analysis of the backward backhand stroke revealed that national squash players showed significant differences compared to international players in several key parameters. Specifically, national players had significantly greater trunk flexion (P = 0.018) and less shoulder medial rotation (P = 0.027). They also had lower racket velocity in the X-direction (P = 0.043). However, there were no significant differences in trunk lateral flexion (P = 0.487), trunk rotation (P = 0.293), shoulder extension/flexion (P = 0.396), elbow flexion/extension (P = 0.818), wrist flexion/extension (P = 0.177), wrist rotation (P = 0.476), racket pitch (P = 0.112), racket velocity in the Y-direction (P = 0.587), or racket velocity in the Z-direction (P = 0.327). Additionally, data for racket yaw, racket roll, and racket Vx were not provided with significant values, indicating that these parameters do not show significant differences. Conclusion International level players outperformed national level players in squash stroke accuracy and control. Key kinematic factors influencing accuracy include trunk forward flexion, shoulder abduction, shoulder internal rotation, and racket angles. The study recommends that coaches design training to enhance technical details and positional control to improve squash performance.
Keywords: Squash; Biomechanical analysis; Backhand stroke; Skill level; Stroke accuracy